SMALL AIRPORT GOVERNANCE AND EFFICIENCY IMPLICATIONS FOR REGIONAL SOCIOECONOMIC INDICATORS IN AIR TRANSPORT - Valim, Gabriel de Aquino; Santos, Ana Carolina Almeida dos; Caetano, Mauro (Revista Gestão Organizacional, 2024)
Purpose: This study centers on assessing the governance structures and efficiency of small airports, which are key determinants of their competitiveness and potential impact on regional socioeconomic indicators, given the strategic relevance of small airports for regional development and national integration. Method/approach: The study has evaluated twenty-five small Brazilian airports as its focal points, employing different analytical methods, including Data Envelopment Analysis, Weight Constraint without Consideration of Satisfactory Levels, Multiple Linear Regression, Linear Correlation, and the Tobit method. Main findings: The findings furnish data inputs for regression analyses, which delineate the infrastructure and organizational characteristics and ascertain their respective levels of significance. Variables such as GDP per capita, population size, proximity to the nearest airport relative to the serviced municipality, frequency of flight delays, and airport attraction index emerge as substantial attributes poised to enhance the efficiency of small airports and foster regional development. Theoretical, practical/social contributions: The main contributions of this study revolve around the efficiency analyses conducted on small airports with diverse governance structures, along with their primary implications for regional development. Originality/relevance: This study holds relevance in its comprehensive examination of both the existing literature and practical dimensions concerning the efficiency and governance of small airports, a topic that is underrepresented in current literature. By spotlighting key variables and elucidating their significant roles in air transportation and regional development, the research fills a gap in the state-of-the-art.